Effectiveness of Centralized Wastewater Treatment Plant in Removing Emerging Contaminants : A Case Study at Kuching, Malaysia - King Kuok, Kuok; Po Chan, Chiu; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri; Mei Yun, Chin (Scientific Research Publishing, 2022)
Before the construction of the Kuching Centralized Wastewater Treatment System Package 1 (KCWTSP1), partially treated blackwater and greywater were discharged directly into natural waterways. The accumulated wastewater had polluted Sarawak river, which is regulated and cannot discharge freely into the South China Sea. The polluted Sarawak river has endangered human health, river water quality, and aquatic ecosystems. Hence, the KCWTSP1 commissioned in 2015 serves the purpose of removing pollutants from wastewater before it is discharged into natural waterways. However, the effectiveness of KCWTPP1 is unknown. This paper is aimed to discuss and review the effectiveness of KCWTPP1 in treating wastewater since its inception in 2015. From 2017 to 2020, KCWTPP1 has treated an average of 4,200,000 m3 of wastewater per year. Generally, most of the discharge effluent met Environmental Quality Act (1974) Standard A criteria, except for the oil and grease parameter. Initially, the plant could not treat suspended solids and total phosphorus, but this was greatly improved in subsequent years. Therefore, some improvements are required to treat oil and grease parameters effectively and efficiently to ensure that only Standard A effluent is discharged into the Sarawak River in the future.